2013
DOI: 10.1248/bpb.b12-00930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moxifloxacin on Serum Glucose Concentrations in Rats

Abstract: Moxifloxacin, a fluoroquinolone antimicrobial agent, has been reported to cause serum glucose abnormalities such as hyper-and hypoglycemia. The purpose of the present study was to investigate the effect of moxifloxacin on serum glucose concentrations in rats. Rats were intravenously injected with moxifloxacin and samples of their arterial blood were collected periodically. Serum glucose concentrations increased with moxifloxacin at 100 mg/kg, and temporal elevations were observed in serum epinephrine and hista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…12,[22][23][24] On the other hand, the single intravenous injection of olanzapine did not affect the serum concentration of histamine (Fig. 4B).…”
Section: Discussionmentioning
confidence: 86%
“…12,[22][23][24] On the other hand, the single intravenous injection of olanzapine did not affect the serum concentration of histamine (Fig. 4B).…”
Section: Discussionmentioning
confidence: 86%
“…Our previous reports demonstrated that fluoroquinolone antimicrobial agents can induce histamine release leading to an increase in serum epinephrine concentrations and hyperglycemia. [7][8][9] In contrast, a single intravenous injection of clozapine increased the serum glucose levels without histamine release. Olanzapine also induced hyperglycemia without affecting the serum concentration of histamine.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that novel fluoroquinolone antimicrobial agents such as gatifloxacin, levofloxacin, and moxifloxacin increased serum glucose concentrations in rats, in association with the induction of histamine release by these drugs, leading to elevations in serum adrenaline concentrations. [6][7][8][9] In contrast, a single intravenous injection of olanzapine increased the serum glucose and adrenaline levels without histamine release. 10) These results suggest that the mechanisms responsible for drug-induced elevations in serum glucose levels vary among these drugs.…”
mentioning
confidence: 94%
“…Moxifloxacin at 100 mg/kg induced histamine release, leading to increased concentrations of epinephrine and glucose in rats. 18 In contrast, a very comprehensive analysis including phase II/III clinical studies and postmarketing studies revealed that moxifloxacin did not affect glucose levels, and alterations in glucose levels were similar in patients with diabetes compared to those without diabetes mellitus. 19 In the present case, hyperglycemia might have been precipitated by 2 factors: lobar pneumonia and moxifloxacin-induced ADR.…”
Section: Discussionmentioning
confidence: 98%